How to do things with words in Judaism - Mashiaḥ, Amir (Journal for the study of religions and ideologies, 2023)
This article aims to investigate Verbal language in the relationship between man and man, and compare it to that between man and God, according to Halakha. I will focus on these two categories, in particular in issues dealing with Proprietary rights. Does Verbal language have any binding in Halakha? Can Verbal language create an actual contract between man and man or between man and God? I will make use of the theories of John Austin in his book How To Make Things With Words. I'll show that in Israeli Law, Verbal language indeed creates a new legal status. However, according to Halakha, dealing with the relationship between man and man, Verbal language has no legal binding. One must perform a physical deed such as moving or lifting the object, in order to create a commitment.According to Halakha, pertaining to the relationship between man and God, there is a tremendous significance to Verbal language. In such a way Austin would define it as a Performative Speech act. In order to explain the difference between the two categories, I'll turn to the idealistic philosophy of Fichte, who defined two concepts of the "Self": the realistic Self and the idealistic one. Accordingly, I'll show the dichotomy of the Performative Speech act in Halakha.